Spirulina (Arthrospira) cultivation in photobioreactors: From biochemistry and physiology to scale up engineering - Guoyu Ma; Qiping Gao; Lu Yuan; Yu Chen; Zhongzhen Cai; Liang Zhang; Jun Hu; Yunjun Wang; Shusong Wu; Yahui Sun (Bioresource Technology, 2025)

Evaluation and simulation of terrestrial latent heat flux globally: A collaborative effort utilizing CMIP6 climate models and eddy covariance observations - Xinling Tian; Zhenhua Di; Yunjun Yao; Zhenwei Liu; Hao Meng; Huiying Sun; Xueyan Wang; Wenjuan Zhang (Agricultural and Forest Meteorology, 2025)

Identification and characterization of a novel type II toxin-antitoxin system in Aeromonas veronii - Caihong Ji; Ting He; Binbin Wu; Xiaomei Cao; Xiaping Fan; Xia Liu; Xiaodan Li; Miao Yang; Jihan Wang; Ling Xu; Shengbiao Hu; Liqiu Xia; et al. (Archives of Microbiology, 2024)

Discovery of an antitumor compound from xenorhabdus stockiae HN_xs01 - Xiyin Huang; Qiong Tang; Siqin Liu; Chen Li; Yaoguang Li; Yunjun Sun; Xuezhi Ding; Liqiu Xia; Shengbiao Hu (World Journal of Microbiology and Biotechnology, 2024)

Enhanced lignin-first valorization of biomass for producing monophenols over Ru/C cooperated with H2WO4 - Ziyu Jia; Jun Hu; Ping Lu; Yahui Sun; Yunjun Wang (Fuel, 2023)

A new isolate of Streptomyces lateritius (Z1‐26) with antibacterial activity against fish pathogens and immune enhancement effects on crucian carp ( Carassius auratus ) - Yahui Yang; Duo Jin; Wensu Long; Ximiao Lai; Yunjun Sun; Feng Zhai; Pan Wang; Xixun Zhou; Yibo Hu; Liqiu Xia; Ganfeng Yi (Journal of Fish Diseases, 2023)
The Streptomyces lateritius Z1‐26 was isolated from soil samples which showed broad‐spectrum antibacterial activity against a broad range of fish pathogens. The In Vivo Imaging System (IVIS) monitored that strain Z1‐26 could survive and colonize in the gills and abdomen of crucian carp. The effects of dietary supplementation with strain Z1‐26 were evaluated with respect to the growth performance, antioxidant capacity, and immune response of crucian carp. The results showed that the Z1‐26‐fed fish had a significantly higher growth rate than the fish fed the control diet. The immune and antioxidant parameters revealed that the non‐specific immune indicators (AKP, SOD, and LZM) of the serum, the expression of immune‐related genes ( IgM , C3 , and LZM ), and antioxidant‐related genes ( Nrf2 and Keap1 ) of the immune organs were significantly increased, whereas the expression of pro‐inflammatory factors ( IL‐1β , IL‐8 , and TNF‐α ) of the immune organs was significantly down‐regulated in crucian carp fed strain Z1‐26 compared with fish fed a control diet. Moreover, fish fed with Z1‐26 supplemented diets showed a significantly improved survival rate after Aeromonas hydrophila infection. In addition, the whole genome analysis showed that strain Z1‐26 possesses 28 gene clusters, including 6 polyketide synthetase (PKS), 4 non‐ribosomal peptide‐synthetase (NRPS), 1 bacteriocin, and 1 lantipeptide. In summary, these results indicated that strain Z1‐26 could improve the growth performance and disease resistance in crucian carp, and has the potential to be developed as a candidate probiotics for the control of bacterial diseases in aquaculture.

Role of polyamide microplastic in altering microbial consortium and carbon and nitrogen cycles in a simulated agricultural soil microcosm - Xia Sun; Ruidong Tao; Daoqing Xu; Mengjie Qu; Mingming Zheng; Meng Zhang; Yunjun Mei (Chemosphere, 2023)

Analysis of VOC emissions and O3 control strategies in the Fenhe Plain cities, China - Yafei Liu; Peipei Qiu; Kai Xu; Chenlu Li; Shijie Yin; Yunjun Zhang; Yu Ding; Chen Zhang; Zheng Wang; Ruixiao Zhai; Yijun Deng; Fengyu Yan; et al. (Journal of Environmental Management, 2023)

Low-Cd wheat varieties and soil Cd safety thresholds for local soil health management in south Jiangsu province, east China - Pengjie Hu; Feng Tu; Simin Li; Yunjun Pan; Cheng Kong; Xumei Zhang; Shaohua Wang; Yongquan Sun; Dan Qiu; Longhua Wu; Yongming Luo; Peter Christie (Agriculture, Ecosystems & Environment, 2023)

Simultaneous nitrification and denitrification by Pseudomonas sp. Y-5 in a high nitrogen environment - Xiaoying Zhang; Yuxiang Xia; Yiwei Zeng; Xia Sun; Ruidong Tao; Yunjun Mei; Mengjie Qu (Environmental Science and Pollution Research, 2022)

iTRAQ analysis reveals the effect of gabD and sucA gene knockouts on lysine metabolism and crystal protein formation in Bacillus thuringiensis - Zixian Yi; Tong Zhang; Junyan Xie; Zirong Zhu; Sisi Luo; Kexuan Zhou; Pengji Zhou; Wenhui Chen; Xiaoli Zhao; Yunjun Sun; Liqiu Xia; Xuezhi Ding (Environmental Microbiology, 2021)
Summary Lysine metabolism plays an important role in the formation of the insecticidal crystal proteins of Bacillus thuringiensis (Bt). The genes lam , gabD and sucA encode three key enzymes of the lysine metabolic pathway in Bt4.0718. The lam gene mainly affects the cell growth at stable period, negligibly affected sporulation and insecticidal crystal protein (ICP) production. While, the deletion mutant strains of the gabD and su c A genes showed that the growth, sporulation and crystal protein formation were inhibited, cells became slender, and insecticidal activity was significantly reduced. iTRAQ proteomics and qRT‐PCR used to analyse the differentially expressed protein (DEP) between the two mutant strains and the wild type strain. The functions of DEPs were visualized and statistically classified, which affect bacterial growth and metabolism by regulating biological metabolism pathways: the major carbon metabolism pathways, amino acid metabolism, oxidative phosphorylation pathways, nucleic acid metabolism, fatty acid synthesis and peptidoglycan synthesis. The gabD and sucA genes in lysine metabolic pathway are closely related to the sporulation and crystal proteins formation. The effects of DEPs and functional genes on basic cellular metabolic pathways were studied to provide new strategies for the construction of highly virulent insecticidal strains, the targeted transformation of functional genes.

Antagonistic activity and protective effect of a Bacillus subtilis isolate against fish pathogen Edwardsiella piscicida - Xiaomeng Ren; Binbin Wu; Feng Zhao; Lingling Qi; Xianfeng Qiu; Ran Li; Sisi Yang; Fuguo Liu; Ganfeng Yi; Xuezhi Ding; Liqiu Xia; Yunjun Sun (Fisheries Science, 2019)

Land use and land cover classification using Chinese GF-2 multispectral data in a region of the North China Plain - Kun Jia; Jingcan Liu; Yixuan Tu; Qiangzi Li; Zhiwei Sun; Xiangqin Wei; Yunjun Yao; Xiaotong Zhang (Frontiers of Earth Science, 2019)

Detection of Toxin Proteins from Bacillus thuringiensis Strain 4.0718 by Strategy of 2D-LC–MS/MS - Qi Yang; Sijia Tang; Jie Rang; Mingxing Zuo; Xuezhi Ding; Yunjun Sun; Pinghui Feng; Liqiu Xia (Current Microbiology, 2015)

Effect of Different Iodine Concentrations on Well-Differentiated Thyroid Cancer Cell Behavior and its Inner Mechanism - Jun Xiang; Xuemei Wang; Zhuoying Wang; Yi Wu; Duanshu Li; Qiang Shen; Tuanqi Sun; Qing Guan; Yunjun Wang (Cell Biochemistry and Biophysics, 2015)

Improved Insecticidal Toxicity by Fusing Cry1Ac of Bacillus thuringiensis with Av3 of Anemonia viridis - Fu Yan; Xing Cheng; Xuezhi Ding; Ting Yao; Hanna Chen; Wenping Li; Shengbiao Hu; Ziquan Yu; Yunjun Sun; Youming Zhang; Liqiu Xia (Current Microbiology, 2014)

Construction and characterization of the interdomain chimeras using Cry11Aa and Cry11Ba from Bacillus thuringiensis and identification of a possible novel toxic chimera - Yunjun Sun; Qiang Zhao; Dasheng Zheng; Xuezhi Ding; Jingfang Wang; Quanfang Hu; Zhiming Yuan; Hyun-Woo Park; Liqiu Xia (Biotechnology Letters, 2014)

Tissue-specifically regulated site-specific excision of selectable marker genes in bivalent insecticidal, genetically-modified rice - Zhan Hu; Xuezhi Ding; Shengbiao Hu; Yunjun Sun; Liqiu Xia (Biotechnology Letters, 2013)

Construction of Gene Library of 20 kb DNAs from Parasporal Crystal in Bacillus thuringiensis Strain 4.0718: Phylogenetic Analysis and Molecular Docking - Feng Wu; Xinmin Zhao; Yunjun Sun; Wenping Li; Liqiu Xia; Xuezhi Ding; Jia Yin; Shengbiao Hu; Ziquan Yu; Ying Tang (Current Microbiology, 2012)

Influence of Mutagenesis of Bacillus thuringiensis Cry1Aa Toxin on Larvicidal Activity - Chunyan Zhang; Liqiu Xia; Xuezhi Ding; Fan Huang; Huanfa Li; Yunjun Sun; Jia Yin (Current Microbiology, 2011)

A Cry1Ac Toxin Variant Generated by Directed Evolution has Enhanced Toxicity against Lepidopteran Insects - Shiping Shan; Youming Zhang; Xuezhi Ding; Shengbiao Hu; Yunjun Sun; Ziquan Yu; Shiquan Liu; Zhou Zhu; Liqiu Xia (Current Microbiology, 2011)

lip2, a novel lipase gene cloned from Aspergillus niger exhibits enzymatic characteristics distinct from its previously identified family member - Jiangke Yang; Jin Sun; Yunjun Yan (Biotechnology Letters, 2010)

Improving the Insecticidal Activity by Expression of a Recombinant cry1Ac Gene with Chitinase-Encoding Gene in Acrystalliferous Bacillus thuringiensis - Xuezhi Ding; Zhaohui Luo; Liqiu Xia; Bida Gao; Yunjun Sun; Youming Zhang (Current Microbiology, 2008)

Detection of chromosomally located and plasmid-borne genes on 20 kb DNA fragments in parasporal crystals from Bacillus thuringiensis - Yunjun Sun; Wei Wei; Xuezhi Ding; Liqiu Xia; Zhiming Yuan (Archives of Microbiology, 2007)

Identification Homologous Recombination Function from Haloarchaea Plasmid pHH205 - Yunjun Mei; Dong Chen; Dongchang Sun; Xiaojuan Wang; Yuping Huang; Xiangdong Chen; Ping Shen (Current Microbiology, 2007)

Identification of cry-Type Genes on 20-kb DNA Associated with Cry1 Crystal Proteins from Bacillus thuringiensis - Liqiu Xia; Yunjun Sun; Xuezhi Ding; Zujiao Fu; Xiangtao Mo; He Zhang; Zhiming Yuan (Current Microbiology, 2005)